Perinatal Weight and Risk of Prenatal and Postpartum Depressive Symptoms - Ertel, Karen A. (Ann Epidemiol, 2017)
PURPOSE: Pre-pregnancy obesity and weight changes accompanying pregnancy (gestational weight gain and postpartum weight retention) may be associated with risk of maternal depressive symptoms during pregnancy and in the postpartum. The few studies that have examined these relationships report conflicting findings. METHODS: We studied pregnant (n=2112) and postpartum (n=1686) women enrolled in Project Viva. We used self-reported pre-pregnancy and postpartum weight and measured prenatal weight to calculate pre-pregnancy body mass index (BMI), gestational weight gain (GWG), and postpartum weight retention (PPWR) at 6 months after birth. We assessed elevated depressive symptoms (EDS) with the Edinburgh Postnatal Depression Scale (≥ 13 on 0–30 scale) at mid-pregnancy and 6 months postpartum. We used logistic regression to estimate the odds of prenatal and postpartum EDS in relation to pre-pregnancy BMI, GWG, and PPWR. RESULTS: 214 (10%) participants experienced prenatal EDS, and 151 (9%) postpartum EDS. Neither pre-pregnancy BMI nor GWG were associated with prenatal EDS. Pre-pregnancy obesity (BMI≥30 kg/m(2)) was associated with higher odds of postpartum EDS (OR=1.69, 95% CI: 1.01, 2.83) compared to normal pre-pregnancy weight in a model adjusted for age, race/ethnicity, nativity, education, marital status, household income, parity, pregnancy intention, and smoking. CONCLUSIONS: Pre-pregnancy obesity is associated with elevated depressive symptoms in the postpartum period. Given the current obesity epidemic in the US and the consequences of perinatal depression, additional depression screening in this population may be warranted.